Anna Wierzbicka’s Linguocultural Theory of Emotions in the Development Dynamics - Svetlana V Ionova; Victor I Shakhovskiy (Russian journal of linguistics: Vestnik RUDN, 2018)
The article overviews the most significant aspects of the linguocultural theory of emotions developed by Anna Wierzbicka. The scientist’s outlook on emotions in the context of language and culture is discussed in its dynamic consistency, starting with the 70-s of the XX century up to the present. The voluminous set of Anna Wierzbicka’s published works on emotions demonstrates the universal and explanatory power of her research method and the systematic character of her linguocultural, semantic and pragmalinguistic studies. The article overviews the vastness and diversity of the issues analysed by the linguist, among which are the emotive semantics of the word, emotional pragmatics of speech, emotional concepts as cultural key words, emotional means of their verbalization in different languages, translation issues, ways of describing emotional scenarios, working out the metalanguage of semantic analysis by using the emotional operator “to feel”, etc. The article does not aim to provide a critical analysis of Anna Wierzbicka’s theory; its unprecedented novelty and topicality as well as the linguist’s innovative method of research, unbelievable hard work, honesty and correctness in defending her scientific views are emphasised.